1999
DOI: 10.1023/a:1020658624567
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 4-Hydroxybutyric acid (4HB) is accumulated in succinic semialdehyde dehydrogenase deficiency, an inherited metabolic disease severely affecting the CNS during postnatal development. Thus, the present study was designed to evaluate the in vitro influence of 4HB on lipid synthesis and CO2 production from [U-14C] acetate in cerebral cortex of 30-day-old Wistar rats. In the presence of 4HB, there was an inhibition of lipid synthesis in cerebral cortex prisms and homogenates. However, no inhibition of lipid synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Interestingly, GHB has been shown to inhibit lipid biosynthesis and to induce oxidative stress in rats [63,64]. Silva and colleagues suggested that altered lipid amounts were not caused by a direct inhibition of the enzymes involved in lipid biosynthesis by GHB, whereas mitochondria were likely to contribute to this effect [64]. These findings again point to the importance of indirect toxic effects in the disease pathogenesis of SSADH-D.…”
Section: Mitochondrial Dysfunction Redox Imbalance and Autophagy Dementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GHB has been shown to inhibit lipid biosynthesis and to induce oxidative stress in rats [63,64]. Silva and colleagues suggested that altered lipid amounts were not caused by a direct inhibition of the enzymes involved in lipid biosynthesis by GHB, whereas mitochondria were likely to contribute to this effect [64]. These findings again point to the importance of indirect toxic effects in the disease pathogenesis of SSADH-D.…”
Section: Mitochondrial Dysfunction Redox Imbalance and Autophagy Dementioning
confidence: 99%
“…However, indirect effects that result in organelle dysfunction or impairment of signaling have been suggested to contribute to SSADH-D. For example, oxidative damage has been shown to be a prominent feature in both patients and in the murine SSADH-D model, and mitochondrial aberrations are frequently observed ( [62] and reviewed in [37]). Interestingly, GHB has been shown to inhibit lipid biosynthesis and to induce oxidative stress in rats [63,64]. Silva and colleagues suggested that altered lipid amounts were not caused by a direct inhibition of the enzymes involved in lipid biosynthesis by GHB, whereas mitochondria were likely to contribute to this effect [64].…”
Section: Mitochondrial Dysfunction Redox Imbalance and Autophagy Dementioning
confidence: 99%
“…Interestingly, GHB has been shown to inhibit lipid biosynthesis and to induce oxidative stress in rats [48,49]. Silva and colleagues suggested that altered lipid amounts were not caused by a direct inhibition of the enzymes involved in lipid biosynthesis by GHB, whereas mitochondria were likely to contribute to this effect [49]. These findings again point to the importance of indirect toxic effects in the disease pathogenesis of SSADH-D.…”
Section: Mitochondrial Dysfuntion Redox Imbalance and Autophagy Defementioning
confidence: 99%
“…However, indirect effects that result in organelle dysfunction or impairment of signaling have been suggested to contribute to SSADH-D. For example, oxidative damage has been shown to be a prominent feature in both patients and in the murine SSADH-D model, and mitochondrial aberrations are frequently observed ( [47] and reviewed in [30]). Interestingly, GHB has been shown to inhibit lipid biosynthesis and to induce oxidative stress in rats [48,49]. Silva and colleagues suggested that altered lipid amounts were not caused by a direct inhibition of the enzymes involved in lipid biosynthesis by GHB, whereas mitochondria were likely to contribute to this effect [49].…”
Section: Mitochondrial Dysfuntion Redox Imbalance and Autophagy Defementioning
confidence: 99%